2018
DOI: 10.1111/head.13396
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of Autonomic Dysfunction Among Those With Persistent Posttraumatic Headache Attributed to Mild Traumatic Brain Injury: A Comparison to Migraine and Healthy Controls

Abstract: Symptoms of autonomic dysfunction were greatest among those with PPTH compared to migraine and healthy controls. Among individuals with PPTH, number of lifetime TBIs was associated with greater symptoms of autonomic dysfunction, while greater headache burden was associated with higher vasomotor domain autonomic dysfunction subscores, potentially indicating that PPTH patients with higher disease burden have an increased risk for having autonomic dysfunction. Symptoms of autonomic dysfunction should be ascertain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 45 publications
2
47
0
Order By: Relevance
“…This was a cross-sectional cohort study in which participants were prospectively enrolled from November 2015 until February 2018. The data reported within this manuscript were collected as part of a United States Department of Defense funded study that aimed to compare clinical characteristics and brain imaging findings amongst those with PPTH vs. migraine [25][26][27] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was a cross-sectional cohort study in which participants were prospectively enrolled from November 2015 until February 2018. The data reported within this manuscript were collected as part of a United States Department of Defense funded study that aimed to compare clinical characteristics and brain imaging findings amongst those with PPTH vs. migraine [25][26][27] .…”
Section: Methodsmentioning
confidence: 99%
“…Poor sleep quality among patients with migraine is significantly associated with headache frequency and headache-related disability [20]. Since PPTH is often phenotypically very similar to migraine [2,21,22], we hypothesized that insomnia would associate with other symptoms similarly in those with PPTH vs. migraine [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that the mechanisms of migraine are likely related to neural and vascular causes, including cerebral cell hyperexcitability, sensitization of the trigeminovascular pathway, genetics, and environmental factors (3). Posttraumatic headache is defined as a headache that develops after a head injury, including mild traumatic brain injury related headache (MBTI-HA) (122). Considering that rTMS has the potential to increase the activity of cortical structures that are involved in pain control or decrease cortical excitability, some studies have attempted to verify whether rTMS is effective for the treatment and prophylaxis of migraine or posttraumatic headache.…”
Section: Headachementioning
confidence: 99%
“…Since PPTH is often phenotypically very similar to migraine (2,21,22), we hypothesized that insomnia would associate with other symptoms similarly in those with PPTH vs. migraine (23)(24)(25).…”
Section: Post-traumatic Headache (Pth) As Currently Defined By the Inmentioning
confidence: 99%